2016
DOI: 10.1111/pala.12228
|View full text |Cite
|
Sign up to set email alerts
|

Telltale eyes: the lateral visual systems of Rhenish Lower Devonian eurypterids (Arthropoda, Chelicerata) and their palaeobiological implications

Abstract: The compound eyes of three taxa of Rhenish Lower Devonian eurypterids are examined and compared with those known from other eurypterids and the extant horseshoe crab Limulus polyphemus. The lateral eyes of the small species Rhenopterus diensti, a phylogenetically basal representative of the stylonurine clade, are characterized by a comparatively low number of lenses and high interommatidial angle Dφ (2.8°). The comparatively limited visual capacities of R. diensti are more similar to L. polyphemus than to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…Some of the oldest fossil arthropods display masticatory spines called gnathobases: tooth-like projections located on the proximal margins of cephalic and trunk appendages [2][3][4][5]. Gnathobases are common in various (typically predatory) arthropod clades throughout the Phanerozoic [2][3][4][5][6][7][8][9][10][11][12]. However, only one extant group has gnathobases developed on a series of appendages: the xiphosurids, true horseshoe crabs [1].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the oldest fossil arthropods display masticatory spines called gnathobases: tooth-like projections located on the proximal margins of cephalic and trunk appendages [2][3][4][5]. Gnathobases are common in various (typically predatory) arthropod clades throughout the Phanerozoic [2][3][4][5][6][7][8][9][10][11][12]. However, only one extant group has gnathobases developed on a series of appendages: the xiphosurids, true horseshoe crabs [1].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, paleontologists have been intrigued by the morphological similarities of L. polyphemus and fossil xiphosurids like Yunnanolimulus luopingensis Zhang et al, 2009 (Guanling Formation, China, Triassic;Hu et al, 2017), Mesolimulus walchi (Desmarest, 1822) (Solnhofen Limestone, Germany, Jurassic; Sekiguchi and Sugita, 1980;Smith and Berkson, 2005) and Limulus darwini Kin and Błaże-jowski, 2014 (Sławno Limestone, Kcynia Formation, Poland, Late Jurassic;Błażejowski, 2015). Finally, L. polyphemus is a useful modern analogue for exploring how extinct gnathobase-bearing arthropods consumed food, including large eurypterids (Selden, 1981;Poschmann et al, 2016), Sidneyia inexpectans Walcott, 1911(Zacaï et al, 2016Bicknell et al, 2018b;Bicknell and Paterson, 2018), and Alacaris mirabilis Yang et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…As shown here, the eye parameter had been applied in trilobites before (Fordyce & Cronin 1989McCormick & Fortey 1998). Its successful application, even to Cambrian arthropods, seems to have triggered a number of analyses of fossil compound eye systems in other arthropods of Cambrian time (Zhao et al 2013), trilobites Tanaka et al 2015), crustaceans (Schoenemann & Clarkson 2012a, b, c;Rust et al 2016;Vannier et al 2016) and eurypterids (Anderson et al 2014;Poschmann et al 2016). It may be concluded that this is indeed an effective way of investigating the structural parameters in the eyes of fossils.…”
Section: Résumé and Perspectivementioning
confidence: 99%
“…Many of these tools can be applied, sometimes in a modified form, to fossils, and this allows an assignment to their ecological habitat and, in particular, the relative depth of the ocean they inhabited. This has been undertaken for the Chengjiang fauna , 2012a and Emu Bay eyes Paterson et al 2011), and also for the excellently preserved arthropods of Bundenbach (Lower Devonian, Hunsrück Shale), which could be assigned to waters up to 200 m depth (Rust et al 2016), as well as for eurypterids (Anderson et al 2014;Poschmann et al 2016) and for a variety of trilobites (Fordyce & Cronin 1989McCormick & Fortey 1998;Schoenemann et al 2008aTanaka et al 2015). Other visual systems in the fossil record, such as those of the Carboniferous shrimps Tealliocaris (Briggs & Clarkson 1985), remain to be investigated.…”
Section: Cambrian Arthropodsmentioning
confidence: 99%